Fermentation and biochemical engineering handbook - Todaro, Celeste L.; Vogel, Henry C. (Elsevier Science, 2014)
A complete reference for fermentation engineers engaged in commercial chemical and pharmaceutical production, Fermentation and Biochemical Engineering Handbook emphasizes the operation, development and design of manufacturing processes that use fermentation, separation and purification techniques. Contributing authors from companies such as Merck, Eli Lilly, Amgen and Bristol-Myers Squibb highlight the practical aspects of the processes-data collection, scale-up parameters, equipment selection, troubleshooting, and more. They also provide relevant perspectives for the different indus.
Includes index.
Keywords: Fermentation.; Biochemical engineering.; elektronické knihy; electronic books